Behaviors of Tall Tiered MSE Walls Reinforced with Geogrid by using Plaxis 2D software - M. E, YADHUNANDAN; SHIVASHANKAR, R. (International Journal of Engineering and Technology, 2018)
Soil is feeble in tension and relatively strong in shear and compression under confinement. Inclusions (or reinforcement) which are strong in tensile resistance are used as reinforcements in a reinforced soil mass. The reinforcement restrains lateral deformation of the surrounding soil through soil reinforcement interface bonding and increases its confinement, reduces its tendency for dilation and consequently increases the stiffness and strength of the soil mass. Over the past 20 years,popularity of reinforced soil structures including slopes,retaining walls, roadways, embankments, and load-bearing foundations have increased.Over the last 20 years Mechanically Stabilized Earth (MSE) structures have been growingly used in many Central, state and private projects. MSE walls are reliable, constructible, and cost-effective. However, analysis and design of tall MSE walls (higher than 6 to 8 m) has been a challenge for the designers.Â In this research work, Finite-Element Program (FEM) PLAXIS 2D is used to predict the behaviour of 5m, 10m, 15m and 20m high MSE walls by varying the parameters like berm width; backfill and foundation soil strength; strength,Â stiffness and spacing of reinforcement; surcharge on reinforced backfill.